BANK INDONESIA RATE STANDARDS IN DETERMINING THE FINANCING OF MUDHARABAH IN BANK MUAMALAT INDONESIA - Rifqi Arief Aminullah; Rizky Maidan Ilmy; Riyan Gita Suara (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2021)
The purpose of this study was to determine how the effect of BI Rate and profit sharing rate to mudharabah financing income. This research was conducted at PT Bank Muamalat Indonesia which is the first syariah bank that stands in Indonesia which is purely syari'ah. This research is quantitative research, the method used in this research is associative research (relationship) supported by document analysis approach, where the object of research is PT Bank Muamalat Indonesia, the sample used is monthly financial statements of PT Bank Muamalat Indonesia period 2011 -2013. The type of data used is secondary data obtained from financial reports published by BI, OJK and through the official website of PT Bank Muamalat Indonesia. Data analysis method used is descriptive analysis and panel data regression model with significance level 5% or 0,05, then to process data using application Eviews 7. The result of the analysis shows that partial rate of BI Rate and Profit Sharing (TBH) has positive and significant effect to Mudharabah Financing Income, proved by probability value of BI Rate 0,0024 <0,05, and probability value of profit sharing rate 0, 0000 <0.05. Together, the BI Rate and Profit Sharing Ratios have a significant effect on Mudharabah Financing Income, this is evidenced by the value of the probability F statistic 0.000 which is less than 0.05. The variables of the BI Rate and the Profit Sharing Rate have contributed to explain Mudharabah Financing Revenue of 83.3%, while the remaining 16.7% (100% - 83.3%) is explained by other variables not examined or excluded in this research model , so it can be concluded that the BI Rate and profit sharing rate have a positive and significant impact on mudharabah financing income either individually or jointly.